Vibrio cholerae Transmits Through Water Among the Household Contacts of Cholera Patients in Cholera Endemic Coastal Villages of Bangladesh, 2015–2016 (CHoBI7 Trial) - Rahman, Zillur; Rahman, Md. Anisur; Rashid, Mahamud-ur; Monira, Shirajum; Johura, Fatema-Tuz; Mustafiz, Munshi; Bhuyian, Sazzadul I.; Zohura, Fatema; Parvin, Tahmina; Hasan, Khaled; Saif-Ur-Rahman, K. M.; Islam, Nazneen N.; et al. (Frontiers in Public Health, 2018)
Recurrent cholera causes significant morbidity and mortality in cholera endemic estuarine areas of Bangladesh. There have been limited studies to investigate the transmission patterns of V. cholerae associated with cholera in Bangladesh. In this study, we characterized V. cholerae serogroup O1 isolated from 30 cholera patients, 76 household contacts, 119 stored drinking water samples, and 119 water source samples in Bakerganj and Mathbaria, two cholera endemic coastal regions in Bangladesh. Results of phenotypic and molecular characterization of V. cholerae isolates (n=56) confirmed them to be toxigenic belonging to serogroup O1 biotype El Tor (ET), and possessing cholera toxin of the classical biotype (altered ET). Molecular fingerprinting of the V. cholerae O1 of clinical and water origins determined by PFGE of Not-I- digested genomic DNA showed them to be closely related, as the PFGE banding patterns were highly homogenous. Phylogenetic analysis using dendrogram of cholera patients, household contacts, and household groundwater sources showed isolates within households to be clonally linked, suggesting water as an important vehicle of transmission of cholera in the coastal villages of Bangladesh. Transmission of toxigenic V. cholerae O1 through drinking water in cholera endemic rural settings underscores the urgent need for evidence based water, sanitation, and hygiene interventions promoting safe drinking water to prevent morbidity and mortality related to cholera and other enteric infections in Bangladesh.